PENGEMBANGAN SMART SOUND ANALYZER SEBAGAI MEDIA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Rizki Muhamad Sidik; Sri Latifah; Vandan Wiliyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Students’ critical thinking skills in physics have not yet developed optimally, particularly when it comes to the topic of sound waves, which requires experimental activities and data analysis. This study aims to develop the Smart Sound Analyzer as a physics teaching aid to enhance students’ critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The developed product integrates sound sensors, a microcontroller, real-time data monitoring, and worksheets based on critical thinking activities. The results of the study show that the media received a content expert validation score of 99.41%, a media expert score of 87.50%, and an instrument score of 94.37%, all of which fall into the “highly acceptable” category. The response rates for students and educators were 94% and 95.33%, respectively, both falling into the